1990
DOI: 10.1136/bjo.74.6.358
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity function and pituitary adenoma: a study of 40 cases.

Abstract: The authors studied the contrast sensitivity function in 40 patients with pituitary adenoma. It seems to be a good index of compression of the visual pathway in this disease, but it lacks specificity and it cannot be used alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In Grochowski's opinion, the examination of contrast sensitivity is a susceptible method for the determination of visual pathway compression. However, it should not be used separately from other examination methods of the visual system (18). Gutowski et al evaluated 11 patients who had tumors in the sella turcica and had no visual acuity and visual field impairment; however, color contrast sensitivity impairment was found (19).…”
Section: Resultsmentioning
confidence: 99%
“…In Grochowski's opinion, the examination of contrast sensitivity is a susceptible method for the determination of visual pathway compression. However, it should not be used separately from other examination methods of the visual system (18). Gutowski et al evaluated 11 patients who had tumors in the sella turcica and had no visual acuity and visual field impairment; however, color contrast sensitivity impairment was found (19).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have determined great color contrast sensitivity impairment in patients diagnosed with PA [ 24 ]. In Grochowicki et al [ 25 ]'s opinion, the contrast sensitivity examination is a suitable method to determine visual pathway compression. However, it should not be used separately from other examination methods of the visual system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of temporal contrast sensitivity have shown both uniform and low temporal frequency loss of contrast sensitivity in patients with chiasmal compression 48. Studies assessing spatial frequency sensitivity in lesions affecting the suprasellar region have found alterations either to be total or limited to low to medium spatial frequencies only 49. A recent study of psychophysical losses in foveal sensitivity found significant losses in chromatic, luminance, and temporal sensitivities in patients with suprasellar lesions without field defects 50…”
Section: Visual Failurementioning
confidence: 99%